A Triply Divergent Reagent for Glycoprotein Synthesis. Issue 3 (3rd March 2015) - De Munari, Sonia; Schiffner, Torben; Davis, Benjamin G.
Abstract: Chemical synthesis of glycoproteins through three different strategies, from the same reagent, is herein described. The flexibility of this system, which allows the comparison of different linkage motifs between the same glycan and protein, is shown by one‐step diversification of a GlcNAc‐ylating reagent and its application in both site‐specific and non‐site‐specific glycoprotein synthesis to create different conjugates from common representative protein scaffolds. Abstract :